Influencia del pensamiento de Luis Napoleón Dillon, en respuesta a la crisis de la plutocracia, en el período de 1912 a 1925 - Peñaherrera Sanipatin, Paulina Elizabeth (2022)
The Republican era in Ecuador, was part of and witnessed the plutocratic period from 1912 to 1925, where the Ecuadorian social classes experienced a big crisis, and the middle and lower classes were affected but the banking oligarchy was the benefited elite. Thus, with the formation of the First Government Board, Luis Napoleon Dillon, as the Minister of Finance, amended the Stamp and Tax Laws among others, with the only purpose of putting an end to the injustices to all of Ecuador's working-class society. This study is supported by the analytical-synthetic and historical-logical method, which helped to compare the facts that focus on a specific situation. In this case the influence of Dillon. Obtaining as results Dillon's inflationary exaggeration of the crisis and the formation of “Banco Central del Ecuador” as well as the “Casa de la Moneda”